Comparing vitamin B2 versus 5% dextrose in water for optimal ureteric jet visualisation at the time of pelvic reconstructive surgery: A randomised controlled trial. (5th January 2023) - Zhao, Zi Ying; Lovatsis, Danny; Gagnon, Louise; Wang, Stella; Huszti, Ella; McDermott, Colleen D.
Abstract: Objective: To compare preoperative vitamin B2 versus intraoperative cystoscopy distension using 5% dextrose in water (D5W) for ureteric jet visualisation during pelvic reconstructive surgery. Design: Double‐blinded, randomised controlled trial. Setting: Three tertiary hospitals in Toronto, Canada. Population: Adult women undergoing pelvic reconstructive surgery. Methods: Patients were randomised to receive 100 mg of vitamin B2 preoperatively versus bladder distension with D5W intraoperatively. Main outcomes: The primary outcome was the rate of accurate detection of bilateral ureteric jets during cystoscopy. Secondary outcomes included the time elapsed until visualisation, use of intravenous furosemide or fluorescein to assist with visualisation, surgeon satisfaction, and positive urine culture 1 week after surgery. Results: The intervention was completed by 236 patients (vitamin B2 n = 117, D5W n = 119). Preoperative characteristics were similar across groups. Accurate detection of both ureteric jets was high in both groups (vitamin B2 97.4% vs. D5W 90.8%, p = 0.051). The vitamin B2 group had significantly lower use of fluorescein rescue compared with the D5W group (3.4% vs. 11.8%, respectively, p = 0.025). Surgeon satisfaction while using vitamin B2 was significantly higher ( p < 0.001). There were no significant differences in the time elapsed until visualisation, the use of furosemide, or the incidence of positive urine culture at 1 week after surgery. Conclusions: Both preoperative vitamin B2 and intraoperative cystoscopy distension with D5W are highly available and inexpensive methods to detect ureteric jets with high accuracy at the time of pelvic reconstructive surgery. Vitamin B2 was shown to have lower rates of fluorescein rescue for visualisation and higher rates of surgeon satisfaction. Abstract : This article includes Author Insights, a video abstract presented by Zi Ying Zhao available at: https://vimeo.com/785903093 .